Determination and characterization of the junction angles in river channels in Brazil with Google Earth Pro images - Pereira, Marco Alésio Fiqueiredo; Alves, Amanda de Souza; Kobiyama, Masato (Revista Brasileira de Geomorfologia, 2024)
The determination of the junction angles and the river dynamics that form them have been studied since the 1930s. These studies normally have three approaches: reduced models, field investigation, and numerical simulation. To collaborate the scientific advances in this topic, the present study proposes a new methodology to determine junction angles in river channels, based on the Cosine Law, employing high-resolution remote sensing imagery. To verify your performance, 135 confluences located in six Brazilian biomes have been analyzed. These confluences were characterized with different magnitudes of channel width and different angles. Thus, relationship between width of the channels and their junction angles were evaluated, it has been obtained values α between 79° and 101°, values β between 133° and 150° and values γ between 117° and 140°. Results show that the channel width influences the magnitude of the junction angles.